SIGNIFIKANSI KEBIJAKAN “Open-Door Policy” TURKI DI BAWAH PRESIDEN TAYYIP ERDOGAN - Rafi Ramadhan Wiryawan; Amalia Azzahra; Dilla Andieni Nurshadrina; Audrey Chairunnisa Imanjaya (Universitas 17 Agustus 1945 Jakarta, 2021)
The civil war that occurred in Syria has since made many Syrians flee to various countries and one of them is Turkey. Since the beginning of the civil war in Syria, Turkey has implemented an open policy for Syrians. In the formulation of foreign policy, there are many variables that need to be considered, namely the environment and international situation and the personality of the leader. Given the strong leadership influence in Turkey's political life, such an approach promises many variations in the foreign policy outcome. The research method used was James Rosenau's adaptive model by looking at external and internal situations as research variables. Apart from that, the individual factor, namely President Tayyip Erdoğan's personality as a decision-maker is considered. The analysis technique used is literature and literature study with qualitative analysis. The writing of this scientific paper is aimed at answering what factors influenced the Turkish Government regarding its Open Door policy in the era of President Erdoğan.